2017
DOI: 10.1002/j.1681-4835.2017.tb00602.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Mapping Study of Information Technology for Development in Agriculture (The Case of Developing Countries)

Abstract: With its rapid proliferation in the developing world, information and communication technology (ICT) has been accepted as an opportunity to assist disadvantaged people. Many projects have piloted ICT supporting rural communities in developing countries. Such rural communities are socially complex and infrastructurally weak environments that demand clear understanding of the social, economical, cultural and political preconditions when implementing ICT innovations. To provide a comprehensive overview of what ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 66 publications
0
45
0
Order By: Relevance
“…Mbuyisa and Leonard () reported that four studies out of 21 empirical studies had used SLF. A few individual studies deployed SLF in other reviews (Duncombe & Boateng, ; Johnston et al, ; Thapa & Sæbø, ; Zewge et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Mbuyisa and Leonard () reported that four studies out of 21 empirical studies had used SLF. A few individual studies deployed SLF in other reviews (Duncombe & Boateng, ; Johnston et al, ; Thapa & Sæbø, ; Zewge et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…This group includes ICT—Rural Poverty linkages framework; the framework of the impact of ICTs on growth/poverty reduction among micro and small enterprises (MSEs); and growth model, as indicated by Mbuyisa and Leonard (). Other models include the mobile telephones impact model, as reported by Donner and Escobar (); Constructive Technology Assessment Approach, as reviewed by Zewge et al (); and the concept of technology appropriation, as indicated in other reviews (Zaremohzzabich et al, ; Zewge et al, ). Some of the concept‐based approaches were deployed to assess the transformational impact of ICTs, which include the ripple effect of technologies as reported by Duncombe and Boateng ().…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a review of studies on Information and Communication Technology for Development (ICT4D), between 2000 and 2010, Gomez () observed that the focus of ICT4D was on business, and only 6% of studies focused on agriculture. Zewge, Dittrich, and Bekele () made a similar observation reviewing studies between 2006 and 2014. People in rural areas are poor for many reasons, including lack of information.…”
Section: Introductionmentioning
confidence: 61%